Social guarantees for workers in Iraq between heritage and contemporary - Abdulnabi, Ahmed Abdulwahab (Al-Adab Journal, 2019)
Our research, entitled "Social Safeguards for Workers in Iraq, between Heritage and Contemporaryity", dealt with a number of historical facts and incidents with a social and economic dimension that affected the heritage of the working class in modern Iraq, especially after the rural migration from the countryside to the city resulting in social and economic problems. Limited to the lack of social guarantees for both the worker and the farmer. Our research included three basic points in which we tried to read and follow up the development and development of the labor movement and focus on the material rights and interests of the workers, the realization of their social guarantees and their great importance in shaping the economic life in Iraq.